Evidence on Informal Insurance in Rural Zimbabwe - Hans Hoogeveen (Tinbergen Institute, 2001)
The test on the presence of full insurance that is commonly employed does not take intoaccount that households also rely on buffer stocks to shield their consumption from incomeshocks. In this paper a test is developed that deals with this omission. It is shown that in thepresence of partial insurance, the common test on the degree of informal insuranceunderestimates the degree of protection offered by informal arrangements. This finding haspolicy implications because if the degree of informal insurance is partial, but highnonetheless, targeting of transfers (in case of drought for instance) is of less importancewhile transitory movement out of poverty is limited. In the empirical part the newlydeveloped test is employed for data on rural Zimbabwe. The presence of full insurance isrejected.
Keywords: 330; Agrarversicherung; Selbstversicherung; Informeller Sektor; Simbabwe